2020
DOI: 10.1177/0959683620908641
|View full text |Cite
|
Sign up to set email alerts
|

2500-year cultural sequence in the Massim region of eastern Papua New Guinea reflects adaptive strategies to small islands and changing climate regimes since Lapita settlement

Abstract: Islands present significant technological and ecological challenges for long-term human settlement, with archaeological investigations of islands globally able to shed light on the adaptive plasticity of cultural groups to changing climatic regimes. The Massim islands of eastern New Guinea significantly reduced in size throughout the Holocene (⩽11.7 kya), providing a unique opportunity to investigate the long-term adaptive capabilities of humans to changing island ecosystems. Here, we report a 2500-2300 year c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 54 publications
(75 reference statements)
0
25
0
Order By: Relevance
“…years (1430 AD) came from East Fergusson sources (Shaw et al . 2020b). By contrast, in the northern Massim at the Rainu mounds at Wanigela, 260 km north‐west, only 3% (2/66) of the analysed obsidian dated to between 1000 and 500 calBP (∼950 to 1450 AD) came from East Fergusson (Bird et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…years (1430 AD) came from East Fergusson sources (Shaw et al . 2020b). By contrast, in the northern Massim at the Rainu mounds at Wanigela, 260 km north‐west, only 3% (2/66) of the analysed obsidian dated to between 1000 and 500 calBP (∼950 to 1450 AD) came from East Fergusson (Bird et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has further demonstrated that more intensive settlement of several Massim islands occurred within the last 550–500 years when wetter climatic conditions prevailed and beachfronts rapidly prograded, providing salubrious conditions for sustained coastal settlement (Shaw et al . 2020b). These results lend further support to Egloff's model for ethnographic Kula development.…”
Section: The Kula Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, calcareous Lapita pottery on Nimowa Island dating from 2500 to 2300 cal. BP did not contain volcanic minerals as islands in the southeast Massim are not of volcanic origin (Chynoweth et al, 2020;Negishi and Ono, 2009;Shaw et al, 2020a). An age range of 3250e3150 to 2800-2600 cal.…”
Section: Pottery Introduction Origins and Late Holocene Cultural Inmentioning
confidence: 99%